Perfis colaborativos em grupos para o desenvolvimento profissional de professores - Leite, Cristiana Brasilio (Universidade Federal de São Carlos, 2021)
This paper was developed among a group of teachers from the early years of municipal schools in Sorocaba / SP, in the years of 2018 to 2019. This study aims to present two devices to locate and analyze how a collaborative group is formed and constituted, that is, which profiles those teachers had, based on their interactions, which have as a background to discuss the implementation of scientific literacy (CA) in the classroom in the early years. Respectively, the second device presented in this paper aims to present evidence of professional development from the teachers within the collaborative group and the dimensions covered by teachers. The methodological approach was qualitative, with a collaborative participation, taking place in about a year and a half, which was distributed in 20 face-to-face meetings. These meetings were all recorded, transcribed, and then organized based on categories of analysis. The results from those devices application brought us indicatives about the collaborative profiles from the teachers and their engagement within the group formed, providing positive ideas of teacher training. Concomitantly, we also managed to analyze signs of professional development of teachers according to the dimensions that teachers got involved during the research. The research and the use of devices assures us that the tools presented in this study can be used by professionals in teacher training and in discussions of collaborative study groups, as it corroborates and answers our research questions, being an alternative to compose the policies of teacher training, contributing to the construction of teaching knowledge.
Collaborative profiles in groups for the professional development of teachers
Keywords: Grupos colaborativos; Desenvolvimento profissional de professores; Alfabetização científica; Collaborative groups; Professional development of teachers; Scientific literacy; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO